Uji Validitas Konstruk Leader Member Eexchange - Multi-Dimensional Measure (LMX-MDM) - Jonny Pranata (UIN Syarif Hidayatullah Jakarta, 2016)
Abstract This study tested construct validity of LMX-MDM (leader member exchange-multidimensional measure). LMX (leader member exchange) has four dimensions, and those are affect, loyalty, contribution, and professional respect with 24 items. Test was conducted on 120 workers in one of private company in Jakarta. Analysis method used in this study is Confirmatory Factor Analysis (CFA) using LISREL 8.70 software. Result of this study proves that all of the subscales are fit to measure one factor model.   Abstrak Penelitian ini menguji validitas konstruk dari LMX-MDM (leader member exchange-multi-dimensional measure). LMX (leader member exchange) memiliki empat dimensi yaitu affect, loyalty, contributions, dan professional respect dengan jumlah item sebanyak 24 item. Pelaksanaan tes dilakukan pada karyawan salah satu perusahaan swasta di Jakarta berjumlah 120 orang. Metode analisis yang digunakan dalam penelitian ini adalah CFA (confimatory factor analysis) dengan bantuan software lisrel 8.70. Hasil pengujian membuktikan bahwa semua subskala fit (sesuai) mengukur model satu faktor. DOI : 10.15408/jp3i.v5i1.9245